Studies of Z-scheme WO3-TiO2/Cu2ZnSnS4 ternary nanocomposite with enhanced CO2 photoreduction under visible light irradiation. Issue 37 (April 2020) - Raza, Adil; Shen, Honglie; Haidry, Azhar Ali; Sun, Luanhong; Liu, Rui; Cui, Shusong
Graphical abstract: Highlights: Novel WO3 -TiO2 /CZTS ternary photocatalyst was prepared via hydrothermal method. CO2 photoreduction performance of ternary photocatalyst improved remarkably. Large surface area and effective charge separation increased the yield rates of CO/CH4 . The WO3 -TiO2 /CZTS ternary photocatalyst showed excellent stability. Abstract: To date, the rapid increase of the CO2 concentration in the Earth's atmosphere is one of the primary causes of global warming, which leads to other environmental issues; however, the photocatalytic CO2 reduction is a process that offers environmental protection and valuable solar fuels generation simultaneously. Yet, the high CO2 activation barrier and inefficient proton supply are the main challenges, which substantially hamper the photo-conversion efficiency over heterogeneous catalysts. Herein, a Z-scheme mesoporous WO3 -TiO2 /CZTS ternary photocatalyst was synthesized through a two-stage strategy, and the photoreduction of CO2 with H2 O vapor was carried out under the visible light irradiation. A synergistic effect among WO3, TiO2 and CZTS over CO2 reduction was observed by anchoring the CZTS over WO3 -TiO2 nanocomposite. The ternary composite showed the enhanced CO/CH4 yield rates of 15.37/1.69 μmol h −1 g −1, which was significantly higher than that of pristine TiO2 (0.44/0 μmol h −1 g −1 ) and WO3 -TiO2 composite (5.39/ 0.34 μmol h −1 g −1 ), attributing the high surface area with greater light absorption and suppressed the electron–hole recombination as a result of the intrinsic p–n heterojunction nature of the material. The apparent quantum efficiency was estimated to be 0.52 %. In addition, the possible reaction mechanism and pathways of photocatalytic CO2 reduction with H2 O over heterogeneous catalysts were also presented.